Bare-hand 3D drawing - Lau, Yan Ling. (2012)
Traditional drawings are usually completed in 2 dimensional (2D) forms using either computer software like Microsoft Paint or using physical tools like pencil or crayons to draw on paper. With the recent advancement in computing devices, people can now draw in the 3 dimensional (3D) spaces or in other words, to be able to “draw” in the air. Camera-based vision technology enables the detection of hands and even fingers with their movements, thus making it possible for users to draw by just moving their bare hands. For this project, a mixed reality 3D drawing program is developed for bare hand interactions. For the purpose of this paper, the 3D drawing program will be referred to as the application and the drawing tool in the application will be referred to as the pencil.